An Improved Topology of Isolated Bidirectional Resonant DC-DC Converter Based on Wide Bandgap Transistors for Electric Vehicle Onboard Chargers - Md. Tanvir Shahed; A. B. M. Harun-Ur Rashid (International Transactions on Electrical Energy Systems)
This article proposes an improved topology for an isolated bidirectional resonant DC-DC converter for electric vehicle (EV) onboard chargers. As opposed to the conventional capacitor-inductor-inductor-inductor-capacitor (CLLLC) resonant converter, the proposed converter’s resonant circuit is composed of a capacitor-inductor-inductor-inductor (CLLL) structure, whose inductances, except the capacitor, can be fully integrated with the leakage and mutual inductances of the high-frequency transformer (HF). Therefore, this offers a smaller size, lower costs, minimal power loss, and eventually higher efficiency. Again, the proposed converter design is based on wide bandgap (WBG) transistor switches that operate at MHz-level switching frequency to achieve high power density, high efficiency, and high compactness. A discrete-time proportional integral derivative (PID) controller has been designed using the phase-shifted pulse width modulation (PSPWM) technique to assure closed-loop control of the proposed CLLL converter. The PID controller parameters have been optimized using both the genetic algorithm (GA) and particle swarm optimization (PSO) algorithm and a comparative analysis has been presented between the two algorithms. To achieve fast switching with very little switching loss, the converter is simulated with several wide bandgap (WBG) switching devices. A performance comparison with conventional Si-based switching devices is also provided. A precise power loss model of the semiconductor switches has been devised from the manufacturer’s datasheet to achieve a perfect thermal design for the converter. A 5 kW CLLL converter with an input range of 400–460 V direct current (DC) and an output range of 530–610 V DC, and a switching frequency of 1 MHz has been designed and investigated under various loading scenarios. Gallium nitride (GaN) switching device-based designs achieved the highest levels of efficiency among the switching devices. The efficiency of this device is 97.40 percent in charging mode and 96.67 percent in discharging mode.